Attitudes of students of Jan Grodek State High Vocational School In Sanok towards organ donation - Lisowska, Diana; Budzińska, Klaudia; Ścieranka, Martyna; Mazur, Anna; Smoleń, Ewa (Journal of Education, Health and Sport, 2017)
Introduction. Transplantology is at a stage of its dynamic development. Despite legal regulations and social campaigns promoting the idea of transplantology, organ donors are missing in Poland. Most Poles are in favor of transplantation, but consenting to transplantation has a number of determinants including sociodemographic, cultural and personal ones. Their cognition allows us to take actions as regards promoting the idea of transplantology and changing the attitudes towards pro-transplantation. Aim of the study. Determination of student attitudes towards organ donation. Materials and methods. The study was conducted in 2017 and covered 355 students of Jan Grodek State High Vocational School in Sanok. Diagnostic survey method and survey technique were used. The research questionnaire was composed of 41 questions. Statistical significance level was assumed to be p <0.05. V-Kramer and Chi squares were used. Results. Most students, especially in medical fields, were supporters of organ transplants, both from living and dead donors. More than half of the respondents in case of a cerebral death would have agreed to donate their organs for transplant. More than half of the students expressed their donation for relatives, and over one quarter of them for the stramgers. More often than not, women declared this. More than half of the respondents would never have been financially financially guided donors, and one in five students strongly opposed to such a practice. Conclusions. Most respondents positively consider their presence in a situation where donor organs are required, both in the face of death and transplantation of a part of their body during the lifetime of relatives or even unrelated recipients. Attitudes of students towards organ donation were altruistic. The students were opposed to financial donations. Attitudes of students were different as regards: gender, place of residence and profile of studies.